2011
DOI: 10.1080/09540121.2010.516331
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of rapid oral fluid HIV testing among male injection drug users in Taiwan, 1997 and 2007

Abstract: Rapid oral fluid HIV testing (rapid oral testing) is in the process of being adapted in Taiwan and elsewhere given its advantages over prior HIV testing methods. To guide this process, we examined the acceptability of rapid oral testing at two time points (i.e., 1997 and 2007) among one of the highest risk populations, male injection drug users (IDUs). For this purpose, an anonymous self-administered survey was completed by HIV-negative IDUs involved in the criminal justice system in 1997 (N (1)=137 parolees) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Our results showed that median price that participants would pay for the oral fluid HIV rapid testing was $6.5 USD, $4.8 USD and $8.1 USD among MSM, FSW and VCT clients respectively. These findings are similar to other studies in which participants were willing to pay no more than $8 USD for oral fluid HIV rapid testing [ 1 , 21 , 37 ]. The vast majority of respondents believed that the cost of oral fluid HIV rapid testing should be federally subsidized [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that median price that participants would pay for the oral fluid HIV rapid testing was $6.5 USD, $4.8 USD and $8.1 USD among MSM, FSW and VCT clients respectively. These findings are similar to other studies in which participants were willing to pay no more than $8 USD for oral fluid HIV rapid testing [ 1 , 21 , 37 ]. The vast majority of respondents believed that the cost of oral fluid HIV rapid testing should be federally subsidized [ 37 ].…”
Section: Discussionsupporting
confidence: 90%
“…Those tests allow individuals to self-administer the oral fluid rapid test and interpret results at their own desired time or location. Moreover, HIV self-testing kits have been found to be acceptable among selected members of high-risk communities, such as male injection drug users [16] and MSM who rarely or never use condoms [17]. However, self-testing kits are typically distributed through pharmacies, clinics, and online stores.…”
Section: Introductionmentioning
confidence: 99%
“…Although diagnostic tests that involve the use of finger-stick blood are well accepted, the advantage of using saliva is that the collection is completely noninvasive and when patients are given a choice, they prefer saliva testing to tests requiring blood. 34,35 …”
mentioning
confidence: 99%